A enunciação de orações canônicas da Igreja Católica - Moura, Deije Machado de (2014)
Playing the role of a prayerful reader, whether a member of the Catholic Church or not, the individual elaborates his own speech (free prayers) and/or uses the texts that are already done and available for use (canonical prayers). In the later case, he identifies himself as the self in the prayer, and make use of the text as if it were his own, and while enunciates it, gives the speech his own unique meaning. From this view, issues concerning the linguistic phenomena of enunciation, more specifically, the enunciation of Catholic Church s canonic prayer are raise and we aim to access how these enunciative approaches may be designed (elements and concepts); in a way we can perceive the otherness manifestation in the process; which may be understood as repeatable or unrepeatable in this kind of enunciation, which differentiates this kind of enunciation from an ordinary one. All this reflection is based on the principles of the theory developed by Oswald Ducrot Teoria da Argumentação na Língua (ANL) as it concerns to this matter, so as in the fundaments found on the base of his studies (Saussure and Benveniste) and texts from his pupils i.e. the researcher Carrel. This theory was chosen as the starting point for our investigation due to its objectivity, coherence, and precision the language aspects study, dismissing the need of resorting to aspects external to it. The corpus selected to our discussion is limited to canonic prayers from the Catholic Church, such as the Our Father and Hail Mary, among others aimed to the saints. After considering the occurrence of this enunciation, comparing to the ideas of the scholars presented on the theoretical basis of this work, we noticed that: the concept of the elements from the catholic enunciation distinguishes in some aspect from those that are nor present in the ordinary enunciation; the speaker and the structure of the praying texts respond for the otherness which rises in the enunciative approach; we notice and explain the repeatability and unrepeatability process in the enunciation of this kind of text; we argue the speaker s discursive attitudes and the impossibility of a reversibility process between speaker and the one he is reaching for, and, finally we propose other investigations on the subject hereby studied: the enunciation of texts elaborated and put into use in the language.